Recent progress of cathode materials for aqueous zinc-ion capacitors: Carbon-based materials and beyond. (15th November 2021) - Sui, Dong; Wu, Manman; Shi, Kaiyuan; Li, Changle; Lang, Junwei; Yang, Yanliang; Zhang, Xiaoyan; Yan, Xingbin; Chen, Yongsheng
Abstract: As an emerging multivalent-ion-based energy storage device, aqueous zinc-ion capacitors (AZICs) combine the merits of zinc-ion batteries with high energy density, excellent safety, low cost and environmental friendliness, and the advantages of supercapacitors with high power density and superior cycling performance. Therefore, AZICs have been considered as a new promising electrochemical energy storage system. Though great progress of AZICs has been made recently, they are still in the infant stage and face many challenges. Specially, the unsatisfactory energy density needs to be improved to realize their practical applications, which calls for high-capacity cathode materials. In this review, after a brief introduction of progress and mechanism for AZICs, we provide a systematical overview of the latest advances in the state-of-art cathode materials. The synthesis route, structure and morphology, electrochemical performance, energy storage mechanism as well as the merits and drawbacks of various cathode materials are comprehensively compared and discussed. Finally, a summary and outlook of the challenges and future perspectives of AZICs were presented. With these, this review might offer some guidance for the future design of dedicated novel cathode materials to realize the great potential of AZICs. Graphical abstract: In this review, we provide a systematical overview of the latest advances in the state-of-art electrode materials for aqueous zinc-ion capacitors (AZICs). The synthesis routes, structure and morphology, electrochemical performance, energy storage mechanism as well as the merits and drawbacks of various cathode materials are comprehensively compared and discussed. In the end, a summary and outlook of the challenges and future perspectives of AZICs are presented. Image 1